Sub-carrier efficient resource allocation for MIMO-OFDMA based cognitive radio / Mohd Zahir Md Kassim - Md Kassim, Mohd Zahir (2014)
Orthogonal Frequency Division Multiple Access (OFDMA) is the access techniques used in Cognitive Radio (CR). By assigning subset Resource Allocation (RA) of subcarrier to individual user, the multiple accesses are achieved in OFDMA whereby low data rate transmission from several users is allowed. The issues are inter-block interference (IBI) and inter-carrier interference (ICI) which will reduce the caparcity. Proposed Subcarrier allocation scheme will be introduced to reduce the interference and also to increase the capacity. Next, different type of diversity techniques will also be used for the subcarrier resource allocation to determine the best performance of OFDMA. The result from diversity research on this MIMOOFDMA will most likely produce a better performance for the STF diversity technique. Besides, by increasing the number of subcarrier will also increase the transmission capacity over number of users.